APLIKASI LIMBAH CAIR PABRIK KELAPA SAWIT DENGAN METODA BIOPORI TERHADAP PERTUMBUHAN TANAMAN KELAPA SAWIT (ELAEIS GUINEENSIS JACQ.) BELUM MENGHASILKAN - Demson Saputra Tambunan; Nelvia Nelvia; Al Ichsan Amri (Jurusan Tanah Fakultas Pertanian Universitas Andalas, 2019)
The wider the area of oil palm plantations in Indonesia, the more palm oil mills will process more oil palm fruit bunches and produce waste one of them is liquid waste. The amount of liquid waste that is more and more if not treated properly will cause environmental pollution. The research aim to study the effect of liquid waste of oil palm factory (LWOPF) with biopori method to the growth of immature oil palm plant. The experiment was conducted in oil palm plantation of Agricultural Faculty of Riau University from May to July 2017. The experiment was arrange drandomized complete design consisting of 13 treatments (without LWOPF; 5; 7.5 and 10 liters LWOPFeachapplied in 1, 2, 3 and 4 biopore/plants), each repeated three times.The parameters observed were plant height, number of midrib, length of midrib, number of leaves, width and length of leaves. The results showed that the application ofLWOPF dose 7.5 liters applied in 4 biopore holes / plants increased addition the number of midrib and the leaves, the width and length of the leaves compared to without LWOPF and the highest than another treatment, but the addition of plant high increased at doses 7.5 liters in 3 biopore/plant and highest than another treatment.Key words : Liquid Wastes of Oil Palm Factory, Biopore Holes, Oil Palm Plants